Peran Teknologi Smartphone Sebagai Media Pembelajaran Interaktif Bagi Mahasiswa di Era Digital - Juita Sipaayung; Munawaroh Munawaroh (Universitas 45 Surabaya, 2025)
The development of smartphone technology has changed the way students access information and learn. Smartphones function as interactive learning media that allow students to engage in the learning process more dynamically. With various educational applications, students can learn anytime and anywhere, increasing the flexibility and effectiveness of learning. In addition, smartphones also facilitate dialogue between students and instructors, as well as among students themselves, which supports collaboration in learning. This study aims to The development of smartphone technology has changed the way students access information and learn. Smartphones function as interactive learning media that allow students to engage in the learning process more dynamically. With various educational applications, students can learn anytime and anywhere, increasing the flexibility and effectiveness of learning. In addition, smartphones also facilitate communication dialogue between students and instructors, as well as among students themselves, which supports collaboration in learning. This study aims to In the contemporary globalized period, communication technology plays a crucial role due to the numerous demands for precise and quick information sharing. Students may now connect with one another without being constrained by time, place, or distance thanks to smartphone technology. According to Pierre Levy, who created the new idea, new media is a theory that examines how media and eras have evolved. The development of smartphone technology has changed the way students access information and learn. Smartphones function as interactive learning media that allow students to engage in the learning process more dynamically. With various educational applications, students can learn anytime and anywhere, increasing the flexibility and effectiveness of learning. In addition, smartphones also facilitate communication both among students and between students and instructors, which supports collaboration in learning. This study aims to The development of smartphone technology has changed the way students access information and learn. Smartphones function as interactive learning media that allow students to engage in the learning process more dynamically. With various educational applications, students can learn anytime and anywhere, increasing the flexibility and effectiveness of learning. In addition, smartphones also facilitate communication both among students and between students and instructors, which supports collaboration in learning. This study aims to In the contemporary globalized period, communication technology plays a crucial role because of the many requirements for fast and accurate information exchange. This smartphone Students can engage with one another through technology without being constrained by time, place, or distance. According to Pierre Levy, who created the new idea, new media is a theory that examines how media and eras have evolved.